Evaluation of partial resheathing of EmboTrap III using the microcatheter (PREMIER) technique for fibrin-rich hard clots in an in vitro vessel model - Namitome, Satoshi; Nagao, Yoichiro; Shigehatake, Yuya; Matsuo, Junichi; Kawamoto, Keisuke; Kuroki, Kenji; Hayashi, Hirotaka; Nakajima, Makoto; Terasaki, Tadashi; Ueda, Mitsuharu; Shindo, Seigo (Frontiers in Neurology, 2024)
Background and purpose Despite the ongoing advancements in mechanical thrombectomy for large vessel occlusions causing acute ischemic stroke, successful recanalization is not achieved in all patients. One contributing factor is the presence of fibrin-rich hard clots. We proposed a new technique called the PREMIER technique, which aims to retrieve fibrin-rich clots. This study evaluated the efficacy of the PREMIER technique on fibrin-rich and erythrocyte-rich clots by comparing it with the simple use of EmboTrap III in an in vitro vessel model. Methods The PREMIER technique involves partially resheathing a fully deployed EmboTrap III (CERENOVUS, Johnson & Johnson Medical Devices, Irvine, California, USA) using a microcatheter to capture and retrieve a hard clot between the inner channel and outer cages of EmboTrap III. We compared recanalization rate of the PREMIER technique with the simple use of EmboTrap III in an in vitro vessel model, occluding the M1 segment with fibrin-rich hard clots (0% erythrocyte composition) and erythrocyte-rich clots (50% erythrocyte composition). Results Among the 40 procedures (10 each for the PREMIER technique and the simple use of EmboTrap III for two different clots) for fibrin-rich clots, the PREMIER technique achieved successful recanalization in all 10 cases, with a significantly higher recanalization rate than the EmboTrap III (100% vs. 50%, p = 0.03). For erythrocyte-rich clots, the recanalization rate was not significantly different in the PREMIER technique compared with the simple use of EmboTrap III (80% vs. 70%, p = 1.00). Conclusion The PREMIER technique is a novel technique for acute large-vessel occlusions caused by fibrin-rich hard clots that hinders successful recanalization during mechanical thrombectomy.